A novel framework for interpreting pyrite-based Fe isotope records of the past. (15th May 2019) - Mansor, Muammar; Fantle, Matthew S.
Abstract: The variation in the iron isotopic composition (δ 56 Fe) of sedimentary pyrite is often interpreted to reflect the degree of Fe redox cycling in modern and ancient environments. However, the degree to which precipitation pathways, isotopic exchange, and precipitation rates can affect the isotopic fractionation associated with pyrite precipitation from aqueous Fe(II) (Fe(II)aq ) is poorly understood. In this study, pyrite is precipitated at 80 °C in batch reactors through the H2 S and polysulfide pathways, in which the precipitation rates and the concurrent formation of a greigite (Fe3 S4 ) phase is modulated by the amount of initially added elemental sulfur and aqueous molybdenum. Our results indicate an average apparent isotopic fractionation (δ 56 Fepyrite - δ 56 FeFeSx, where FeSx includes FeS, Fe(II)aq, and greigite) of −0.51 ± 0.22‰ throughout the experiments irrespective of precipitation pathways and greigite formation. Early-stage precipitation is associated with ∼0.3‰ larger isotopic fractionation than late-stage precipitation, possibly indicating either a rate-dependent kinetic isotope effect (KIE) or a different isotopic fractionation factor for early-stage pyrite nucleation compared to later-stage growth. Overall, the magnitude of the apparent isotopic fractionation is significantly smaller than the <−2‰ isotopic fractionation determined in previous experiments (Guilbaud et al., 2011b). Numerical models indicate that isotopic exchange between pyrite and Fe(II)aq is necessary to explain the experimental data. The inferred rate of isotopic exchange decreases with time in our experiments, likely as a function of particle size, but shows no clear correlation with temperature across different studies. In the presence of isotopic exchange, modeling results indicate that pyrite precipitated from Fe(II)aq may theoretically have δ 56 Fe values ranging from −3 to + 4‰, which spans nearly the whole δ 56 Fe range observed in nature. Negative values reflect the expression of the KIE when isotopic exchange is slow (relative to net precipitation rate) while positive values reflect the expression of the equilibrium isotope effect (EIE) when isotopic exchange is relatively fast. We therefore propose that the variation in sedimentary pyrite δ 56 Fe can be explained in terms of varying expression of the KIE and the EIE, either during different stages of precipitation or as controlled by the availability of Fe(II), sulfide, and oxidants throughout Earth's history. The predominantly negative (but highly variable) pyrite δ 56 Fe values in modern marine sediments suggest a higher expression of the KIE in low temperature systems, but do not rule out the importance of isotopic exchange. The isotopic exchange rate is currently underconstrained in low temperature systems with an uncertainty range that spans 8 orders of magnitude. Our work suggests that isotopic exchange has the potential to affect sedimentary pyrite δ 56 Fe unless the current upper limit for isotopic exchange rate is overestimated by 5 orders of magnitude.